(untitled) (Journal of Applied Membrane Science & Technology, 2024)
Recent interest in nanoparticles-reinforced polymer matrices has surged due to their superior properties over virgin polymers. Nevertheless, there remains a gap in research regarding the impact of clay dispersion on polymeric membranes employed in membrane distillation (MD). This study aims to investigate how the dispersion of Cloisite 15A (C15A) clay influences the structure of polyvinylidene fluoride (PVDF) membranes and improves dye removal efficiency. A nanocomposite membrane consisting of polyvinylidene fluoride-Cloisite 15A clay (PVDF-C15A) was prepared using a phase-inversion process. Additionally, a PVDF membrane without clay was prepared as a control. The influence of clay on the crystalline structure of the PVDF membrane was examined by analyzing morphology, porosity, wetting pressure, contact angle, surface roughness, mechanical strength, and thermal stability. X-ray diffraction spectroscopy and transmission electron microscopy were employed to assess the dispersion state of the clay. The fabricated membranes were evaluated in direct contact membrane distillation for treating dyeing solution. To understand the interaction between dye particles and the membranes, zeta potentials of both the control and nanocomposite membranes were measured. The study revealed that the nanocomposite membrane exhibited higher permeate flux compared to the control membrane. This improvement was primarily attributed to the well-dispersed layered silicate within the nanocomposite membrane, which enhanced its structural properties significantly.